1996
DOI: 10.1111/j.1467-6427.1996.tb00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress and coping in the practice of family therapy: a British survey

Abstract: A sample of 171 members of the Association for Family Therapy (UK) was surveyed and data obtained on their general level of experienced stress, the sources and levels of experienced stresses they encountered in their practica, and the professional and private coping strategies they used to mitigate the effects of these stressors. The results indicate that stress can be experienced in all practice contexts, with important factors in its overall configuration being personal/professionaI worth and agency expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…A study of clinical psychology trainees (Cushway, 1992) found the most frequent coping strategies to be: decreasing tension by exercise, talking with other trainees, friends, partner or supervisor. In UK family therapists (Street and Rivett, 1996), relaxing activities, looking forward to special events, keeping a clear division between work and home and active leisure activities were common coping mechanisms; teamwork may also be a useful coping strategy.…”
Section: Ways Of Copingmentioning
confidence: 99%
“…A study of clinical psychology trainees (Cushway, 1992) found the most frequent coping strategies to be: decreasing tension by exercise, talking with other trainees, friends, partner or supervisor. In UK family therapists (Street and Rivett, 1996), relaxing activities, looking forward to special events, keeping a clear division between work and home and active leisure activities were common coping mechanisms; teamwork may also be a useful coping strategy.…”
Section: Ways Of Copingmentioning
confidence: 99%
“…Their argument is that many features identified within individual work will come to have greater currency within family therapy and this is particularly evidenced by the recent interest in the Rogerian influences in therapy and the continuing interest in psycho-dynamic approaches. This view has several points of interest for the training field, as research into the characteristics of trainees has clearly shown that a considerable proportion come to family therapy with prior experience in individual work (see, for example, Street and Rivett, 1996). Clearly some form of rapprochement within the psychotherapeutic field and the consideration of 'individual' influences is now permissible and trainees' prior experience cannot be neglected.…”
Section: ) the Field Will Become Characterized By Much Less Purity Omentioning
confidence: 99%
“…Street and Rivett (1996) report that 54% of a sample of 171 British family therapists had had personal individual therapy, 24.7% had had couple therapy and 9.4% family therapy. (Some recipients of couple and family therapy had also been recipients of individual therapy.)…”
Section: The Self Of the Therapistmentioning
confidence: 99%